2022
DOI: 10.1002/mus.27715
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in insulin‐like growth factor system in spinal muscular atrophy

Abstract: Introduction/Aims: Spinal muscular atrophy (SMA) is an inherited neuromuscular disease caused by survival motor neuron (SMN) protein deficiency. Insulin-like growth factor-I (IGF-I) is a myotrophic and neurotrophic factor that has been reported to be dysregulated in in vivo SMA model systems. However, detailed analyses of the IGF-I system in SMA patients are missing. In this study, we analyzed the components of the IGF-I system in serum and archived skeletal muscle biopsies of SMA patients. Methods: Serum IGF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
(103 reference statements)
0
6
0
Order By: Relevance
“…A vitro experiment verified that the decreased level of Igfbp5 protein restrained the proliferation and differentiation of bovine skeletal muscle satellite cells ( 91 ). Conversely, in a recent study, increased expression of Igfbp5 was detected in skeletal muscle biopsies of spinal muscular atrophy (SMA) patients and non-SMA neuromuscular diseases ( 92 ). In our study, the decreased expression of Igfbp5 in qPCR validation was also inconsistent with the transcriptome sequencing, which was probably attributed to the difference in muscle tissues or individuals.…”
Section: Discussionmentioning
confidence: 89%
“…A vitro experiment verified that the decreased level of Igfbp5 protein restrained the proliferation and differentiation of bovine skeletal muscle satellite cells ( 91 ). Conversely, in a recent study, increased expression of Igfbp5 was detected in skeletal muscle biopsies of spinal muscular atrophy (SMA) patients and non-SMA neuromuscular diseases ( 92 ). In our study, the decreased expression of Igfbp5 in qPCR validation was also inconsistent with the transcriptome sequencing, which was probably attributed to the difference in muscle tissues or individuals.…”
Section: Discussionmentioning
confidence: 89%
“…Conversely, selective depletion of SMN in motor neurons alone results in a milder SMA phenotype as compared with systemic depletion ( 67 ), while selective restoration of SMN in neural tissue leads to only partial rescue of the SMA phenotype ( 68 ). It is possible that effects on SMA neuromuscular function could be mediated through peripheral organ secretion of neurotrophic factors such as IGF-1, which, together with its binding protein IGFALS has reduced expression in patients and mouse models of SMA ( 64 , 69 ). Further studies to investigate whether non–motor neuron, cell-autonomous SMN rescue in liver and other peripheral organs has a role in motor neuron function and overall survival in SMA patients would increase our understanding of the pathology and natural history of SMA, and clinical implications of extraneuronal and treatment-modified phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoassays from previous research revealed that SMA patients have significantly lower levels of insulin‐like growth factor‐1 (IGF‐1) in their serum 35 . As IGF‐1 is necessary for the general growth of individuals, 36 restoration of the IGF‐1 level would be important for SMA patients whose height and weight have been reported to be lower than those of healthy individuals 37 .…”
Section: Discussionmentioning
confidence: 99%